Analisis Sistem Informasi Registrasi Pasien Dengan Metode Pieces Di Rumah Sakit Mulia Hati Wonogiri - Setyaningrum, Arma; , Sri Darnoto S.KM M.PH; , Arief Kurniawan NP, SKM, M.PH (2015)
Mulia Hati Wonogiri hospital has uses management information system for about 2 years. It is used by administration and reporting especially in the registration. In fact, the office have difficulties on searching of the old patient database in management information system application. It makes the officers performance become hampered. The objective of this study is to analyze the registration information system of patients using PIECES method, namely : Performance, Information, Economy, Control, Efficiency and Service. The researcher uses observation and interview as technique of collecting data. The result of study shows that registration information system work of the patients is less optimal. It result information thaat has not been in time and the cost for taking care of medical resume and treatment of system and hardware is more expensive. The system is not efficient because of the uncomplete system, control and safety in less of control. The service is not maximal enough, since the processes is done uncorrectly. Hence the patients needs more time to take medical service